2020
DOI: 10.1123/jpah.2019-0415
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training on Total Daily Energy Expenditure and Body Composition in Weight-Stable Adults: A Randomized, Controlled Trial

Abstract: Background: The present study examined, among weight-stable overweight or obese adults, the effect of increasing doses of exercise energy expenditure (EEex) on changes in total daily energy expenditure (TDEE), total body energy stores, and body composition. Methods: Healthy, sedentary overweight/obese young adults were randomized to one of 3 groups for a period of 26 weeks: moderate-exercise (EEex goal of 17.5 kcal/kg/wk), high-exercise (EEex goal of 35 kcal/kg/wk), or observation group. Individuals maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…The findings of intervention studies concur with these observations. Human participants exhibit a smaller increase in DEE than expected when prescribed daily exercise levels are increased (Dhurandhar et al 2015;Garland et al 2011;Goran and Poehlman 1992;Hand et al 2020;Herrmann et al 2015;Keytel et al 2005;Willis et al 2020;Wing 1999). Moreover, the longer and greater the exercise intervention, the greater the estimated energy compensation exhibited (for a summary see Pontzer 2018; his Figure 2).…”
Section: Evidence For the Existence Of Energy Compensationmentioning
confidence: 94%
See 2 more Smart Citations
“…The findings of intervention studies concur with these observations. Human participants exhibit a smaller increase in DEE than expected when prescribed daily exercise levels are increased (Dhurandhar et al 2015;Garland et al 2011;Goran and Poehlman 1992;Hand et al 2020;Herrmann et al 2015;Keytel et al 2005;Willis et al 2020;Wing 1999). Moreover, the longer and greater the exercise intervention, the greater the estimated energy compensation exhibited (for a summary see Pontzer 2018; his Figure 2).…”
Section: Evidence For the Existence Of Energy Compensationmentioning
confidence: 94%
“…Many, perhaps most, studies and reviews of energy compensation have assumed that energy-saving changes in NEAT is the process at play (e.g. Goran and Poehlman 1992;Hand et al 2020;Meijer et al 1999;Morio et al 1998), and some work seems to provide indirect evidence for this. For example, an across-school study of children reported that the amount of intense physical activity they undertook at school did not relate to their total levels of activity over the entire day, i.e.…”
Section: Evidence For Reductions In Neatmentioning
confidence: 99%
See 1 more Smart Citation
“…The compensation model assumes that energy budgets are somewhat constrained, which forces trade-offs between energy invested into AEE and BEE, thus predicting a negative relationship between AEE and BEE and therefore b < 1 for the relationship between TEE and BEE. It is currently unknown whether energy compensation in humans occurs only under extreme conditions, or at least only during periods of prescribed exercise, where measured or inferred energy compensation has been documented on several occasions, [16][17][18] or instead whether it is the default model of energy expenditure in humans living typical lives, where activity and energy intake are naturally adjusted over time.…”
Section: Energy Budgets and Competing Hypothesesmentioning
confidence: 99%
“…This is influenced by the level of energy needed and the metabolic used based on the activity and intensity of each teenager. More intense activity stimulates the body's metabolic system into energy and vice versa [37]. Moreover, an exercise program that involve much physical activity for 33 weeks significantly improve students' health and skills in swimming learning [38].…”
Section: Multicollinearity Testmentioning
confidence: 99%